2013
DOI: 10.7326/0003-4819-158-6-201303190-00006
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology, Diagnosis, and Management of Aristolochic Acid Nephropathy

Abstract: It has been 20 years since the first description of a rapidly progressive renal disease that is associated with the consumption of Chinese herbs containing aristolochic acid (AA) and is now termed aristolochic acid nephropathy (AAN). Recent data have shown that AA is also the primary causative agent in Balkan endemic nephropathy and associated urothelial cancer. Aristolochic acid nephropathy is associated with a high long-term risk for renal failure and urothelial cancer, and the potential worldwide population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
141
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 155 publications
(154 citation statements)
references
References 61 publications
2
141
0
11
Order By: Relevance
“…Plant drugs derived from Aristolochia spp. remain in use today for the treatments of snake bites, arthritis and gout, and coronary artery diseases (8,9), particularly in Asia and some other areas, with the potential for further exposure (10). Aristolochia herbs create a potential public health problem of considerable magnitude (11).…”
Section: Introductionmentioning
confidence: 99%
“…Plant drugs derived from Aristolochia spp. remain in use today for the treatments of snake bites, arthritis and gout, and coronary artery diseases (8,9), particularly in Asia and some other areas, with the potential for further exposure (10). Aristolochia herbs create a potential public health problem of considerable magnitude (11).…”
Section: Introductionmentioning
confidence: 99%
“…12 Balkan endemic nephropathy and Chinese herb nephropathy are the same disease, and they are specifically related to UTUC. 13 They are characterized by a mutation of the p53 gene as a consequence of exposure to aristolochic acid. A significant use of aristolochic acid from Aristolochia plants has been documented in Taiwan, where the incidence of UTUC is estimated to be approximately 20-25% of all urothelial cancers, the highest worldwide.…”
mentioning
confidence: 99%
“…Aristolochic acid-induced AKI is characterized by proximal tubular epithelial cell death related to oxidative stress . Experimental studies conducted in rabbits and rats confirmed that aristolochic acid was nephrotoxic and led to the concept of aristolochic acid nephropathies that encompasses CKD in Balkan endemic nephropathy and Chinese herb nephropathy (Gökmen et al, 2013). Animal models confirmed the fibrogenic potential of aristolochic acid in vivo (Cosyns et al, 1994;De Broe, 2012;Debelle et al, 2002) both in chronic use and following AKI.…”
Section: Aristolochic Acid-associated Akimentioning
confidence: 78%